Efek moderasi self-efficacy pada hubungan kepuasan kerja, etika kerja islami, dan komitmen organisasi terhadap produktivitas - Dheannisa Firdha Akbarizqi; Saifudin Saifudin (Journal of Halal Industry Studies, 2024)
This research aims to investigate the impact of job satisfaction, Islamic work ethics, and organizational commitment on productivity, with self-efficacy serving as a moderating variable. This type of research is quantitative, focusing on a population of PT employees. Pan Pacific Jakarta Semarang Branch. The sampling technique used in this research was purposive, involving a total of 350 respondents. The analysis technique used is MRA. Statistical test results indicate that job satisfaction has no significant effect on productivity, whereas Islamic work ethics and organizational commitment have a positive impact on productivity. Through the interaction effect of the moderating variable, self-efficacy moderates both the relationship between job satisfaction and organizational commitment on productivity and the relationship between Islamic work ethics and productivity.